Personalised Digital Marketing Perspectives and Practices in Tourism Industry - Dr. Bijay Prasad Kushwaha, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Digital marketing is becoming popular and every organisation is trying to promote their business through digital adverting platforms. The service industry is known for personalisation where services are personalised as per the requirement of customers. This ensures customer's satisfaction and helps in retaining existing customers. This paper studies the various forms of digital marketing tools that can be applied to destination services marketing in a personalised way. This study covers five digital marketing tools such as search engines, email, banner ads, social media, and online video ads. The convenience sampling techniques used to select 423 respondents from Noida city, India. The finding suggests that email, social media, and online video are more effective personalised digital marketing tools for the tourism industry. Search engine marketing is based on keyword selection therefore personalisation may be difficult. SPSS Amos 23.0 was used to analyse and interpret the empirical data